Breastfeeding self-efficacy and its relationship with breasfeeding duration - De Oliveira Minharro, Michelle Cristine [UNESP]; De Barros Leite Carvalhaes, Maria Antonieta [UNESP]; De Lima Parada, Cristina Maria Garcia [UNESP]; Ferrari, Anna Paula [UNESP] (FapUNIFESP (SciELO), 2019)
Objective: To evaluate maternal self-efficacy in breastfeeding and investigate its effect on breastfeeding duration in Botucatu - São Paulo. Method: Prospective cohort study (n = 650 mothers/children). The mother-infant dyads were selected from July 2015 to February 2016, when the infants had on average 20 days. The short form of the Self-efficacy Scale in Breastfeeding was applied and the lactation status was evaluated at 2, 3, 4, 6, 9 and 12 months. The associations were evaluated through multiple logistic regression and Cox regression models. Results: 77.9% of the mothers showed high self-efficacy in breastfeeding. Mothers with high selfefficacy are 71% (OR = 0.29) and those with medium self-efficacy 52% (OR = 0.47) less likely to stop breastfeeding before 12 months. Conclusion: Breastfeeding self-efficacy has a positive impact on the duration of breastfeeding, supporting its evaluation and promotion in pre and postnatal nursing care.
AUTOEFICACIA EN EL AMAMANTAMIENTO Y EN LA RELACIÓN CON LA DURACIÓN DE LA LACTANCIA MATERNA
AUTOEFICÁCIA NA AMAMENTAÇÃO E A RELAÇÃO COM A DURAÇÃO DO ALEITAMENTO MATERNO
Keywords: Breastfeeding; Child Health; Confidence; Infant; Self-efficacy